2021
DOI: 10.21203/rs.3.rs-528331/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective Effects of Rheum Turkestanicum Janischagainst Diethylnitrosamine-Induced Hepatocellular Carcinoma in Rats

Abstract: Aim of the study Hepatocellular carcinoma (HCC) is common cancer that causes many deaths worldwide. Recent studies have reported anti-cancer effects of R. turkestanicum against various cell lines including leukemia cervical tumor, and breast cancer. In this study, we aimed to identify the effect of R. turkestanicum against diethylnitrosamine (DEN)-induced HCC. Methods Wistar rats were divided into four groups of control, DEN, DEN + 100 mg/kg or 400 mg/kg of hydroethanolic extract of the plant roots. Results Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…It grows in Asia, especially in the northeast of Iran ( Taheri and Assadi, 2013 ). The studies have reported that R. turkestanicum has beneficial effects in treating diabetes, hypertension, and cancer ( Shiezadeh et al, 2013 ; Moradi et al, 2016 ; Boroushaki et al, 2019a ; Moradzadeh, 2019 ; Ghorbani et al, 2021 ). This herb is composed of different chemical components, including anthraquinones (e.g., aloe-emodin, emodin glycosides, physione, and rhein), flavonoids (e.g., epicatechin and quercetin), alkanes (e.g., eicosane and heneicosane), and fatty acids (e.g., linoleic acid and 9-octadecenoic acid) ( Hosseini et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It grows in Asia, especially in the northeast of Iran ( Taheri and Assadi, 2013 ). The studies have reported that R. turkestanicum has beneficial effects in treating diabetes, hypertension, and cancer ( Shiezadeh et al, 2013 ; Moradi et al, 2016 ; Boroushaki et al, 2019a ; Moradzadeh, 2019 ; Ghorbani et al, 2021 ). This herb is composed of different chemical components, including anthraquinones (e.g., aloe-emodin, emodin glycosides, physione, and rhein), flavonoids (e.g., epicatechin and quercetin), alkanes (e.g., eicosane and heneicosane), and fatty acids (e.g., linoleic acid and 9-octadecenoic acid) ( Hosseini et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%